Heart failure in hospitalized patients with diabetic foot ulcers: Clinical characteristics and their relationship with prognosis (糖尿病足溃疡住院患者的心衰：临床特点以及它们与预后的关系). (14th June 2013) - Xu, Lei; Qian, Hongjie; Gu, Junyi; Shi, Jianyuan; Gu, Xueming; Tang, Zhengyi
Abstract: Background: In the present study we: (i) evaluated the incidence of heart failure (HF) in patients with diabetic foot ulcer (DFU); and (ii) investigated the relationship between the clinical characteristics in these patients and prognosis. Methods: The clinical characteristics of 330 consecutive Chinese patients (137 men, 193 women) hospitalized for DFU were collected and assessed to determine the effects of HF on DFU. All patients were followed for 3 months and rates of healing, the development of new ulcers, amputations, and mortality were calculated at the end of the follow‐up period. Results: Heart failure was present in 64.3% of patients with DFU, with the prevalence of HF increasing with Wagner grade from Wagner 1 through to Wagner 5 (42.4%, 59.1%, 64.7%, 73.3%, and 87.0%, respectively), higher than the 33.6% prevalence in diabetic patients without DFU (Wagner 0). The presence of HF conferred a greater increased relative risk of a worse prognosis. The 3‐month healing rates of DFU in patients with and without HF were 60.3% and 75.7%, respectively. Recurrence (13.2% vs 7.5%) and amputations (28.6% vs 20.0%) were more frequent in patients with than without HF ( P  < 0.05). All‐cause mortality was recorded for 14 of 126 patients with HF compared with three of 70 patients without HF (11.1% vs 4.3%, respectively; P  < 0.05). Conclusions: The prevalence of HF is high in Chinese inpatients with DFU, with the presence of HF indicating a worse prognosis for these patients.